Mittelschmerz Syndrome: Exploring the Role of Homoeopathy in Gynecological Pain Disorders (Homoeopathy for All, 2025)
A considerable percentage of  women of reproductive age  experience ovulation discomfort,  also known as Mittelschmerz,  during the mid-cycle period. It  can be distressing and mimic  severe abdominal problems, but it  is usually benign and self-limiting.  Reassurance and symptomatic  treatment are the cornerstones  of conventional management. A  comprehensive therapeutic option,  homeopathy treats both acute pain  and underlying constitutional issues.  The epidemiology, etiopathogenesis,  diagnosis, and homeopathic  treatments of Mittelschmerz are  covered in this article, with a focus  on customized care.
Keywords: Mittelschmerz; Ovulation pain; Homoeopathy; Gynecology; Functional pain syndromes; Oocyte; Ovarian follicles; Follicular phase; Hormones; 1 sided abdominal pain; Mid-cycle pain; Fertility indicator; Follicular rupture; Follicular fluid irritation